2017
DOI: 10.1002/nml.21275
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure of Nongovernmental Development Organizations

Abstract: In the first international study of this kind, we analyze the capital structure of 364 nongovernmental development organizations ( NGDOs ) from three different countries: Belgium, Spain, and the United Kingdom. We observe lower debt ratio values in the United Kingdom, and significant differences between countries were found by testing an econometric model with the five classical determinants of leverage, considering total debt and both long-and short-term debt. We find support for the pecking order theory, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 42 publications
2
13
2
1
Order By: Relevance
“…According to our survey data, the surveyed non-profits wished to have higher than 30 percent of debt in their capital structure, these are levels also reported in other European studies. Garcia-Rodriguez and Jegers (2017) found that average levels for the EU non-profits analysed in their study are more than 32 percent of debt (for Belgium, Spain and the United Kingdom). In our study, we have used macroeconomic indicators for 2014 and 2016 for the Polish environmental conditions.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…According to our survey data, the surveyed non-profits wished to have higher than 30 percent of debt in their capital structure, these are levels also reported in other European studies. Garcia-Rodriguez and Jegers (2017) found that average levels for the EU non-profits analysed in their study are more than 32 percent of debt (for Belgium, Spain and the United Kingdom). In our study, we have used macroeconomic indicators for 2014 and 2016 for the Polish environmental conditions.…”
Section: Resultsmentioning
confidence: 80%
“…Source: own study based on Holmstrom and Tirole (1996and 2001, Garcia-Rodriguez and Jegers (2017), Siekelova et al (2017). Non-profit entities are a kind of entity that are almost identical as for-profit businesses from the organisational side (Garcia-Rodriguez & Jegers, 2017, Rahman et al, 2017a.…”
Section: The Nofdel Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, collaboration between researchers from different countries is required for conducting this type of research, given the great differences between the regulations of each country. In this sense, a preliminary study has been performed (Garcia-Rodriguez & Jegers, 2016). It analyzes the capital structure of NPOs from Belgium, Spain and the UK, showing significant differences depending on the nationality of the organization.…”
Section: General Conclusionmentioning
confidence: 99%
“…No obstante, para llevar a cabo este tipo de trabajos de manera oportuna sería necesaria la colaboración entre investigadores de los distintos países, dadas las grandes diferencias entre las regulaciones de cada país. En este sentido, se ha desarrollado un estudio preliminar (Garcia-Rodriguez & Jegers, 2016) en el que se analiza la estructura de capital de ENLs de Bélgica, Reino Unido y España, mostrando diferencias significativas en función del país de origen de la organización. Esta construcción de muestras internacionales permitiría introducir el efecto de variables institucionales, macroeconómicas y culturales propias de cada país, tal y como se ha realizado en el ámbito empresarial (e.g., Laitinen & Suvas, 2016;Li & Harrison, 2008;Zheng, El Ghoul, Guedhami & Kwok, 2012).…”
Section: Conclusiones Generalesunclassified